Effects of whole-body vibration training frequency on neuromuscular performance: a randomized controlled study - Konstantina Karatrantou; Petros Bilios; Gregory C. Bogdanis; Panagiotis Ioakimidis; Eleutherios Soulas; Vassilis Gerodimos (Termedia Publishing House, 2019)
This study compared the efficacy of two whole-body vibration (WBV) protocols with equal training volume and different frequency of training sessions/week on body composition and physical fitness. Sixty male air force cadets (age: 20.5±1.4 years) were randomly assigned to a lower frequency (Lf-WBV), a higher frequency (Hf-WBV) or a control group (CG). The training volume was equated (20 training sessions) between the two WBV groups, but the number of weekly training sessions was different. The Lf-WBV group trained three times per week, the Hf-WBV group trained five times per week, while the CG did not perform any training. Each training session, for both groups, included 10 sets x 1 min with 1 min rest of WBV on a synchronous vibration platform (25-35 Hz, 4-6 mm). Body composition, flexibility, maximal strength, 30 m sprint time, squat jump (SJ) and countermovement jump (CMJ) performance, Wingate test performance, and 20 m shuttle run performance were evaluated before and after training. Only the Hf-WBV group demonstrated an increase in flexibility +7%; p<0.01; d=0.33) and maximal strength (+10%; p=0.016; d= 0.59), and a significant reduction in fat mass (-6.2%; p<0.01; d=0.21). SJ performance improved to a similar extent in both Hf-WBV and Lf-WBV groups (+7%; p<0.01; d=0.32). There were no changes in any parameter in the CG. In conclusion, only the condensed weekly WBV protocol was effective in improving body composition, flexibility, lower limb strength and power in young active individuals. The WBV protocol with the higher dispersion of training sessions per week (lower training frequency/week) improved SJ performance but did not have any effect on body composition, flexibility, or maximal strength.